Seasonality of infection caused by Epstein – Barr virus - T. V. Solomay; N. N. Filatov (Журнал инфектологии, 2020)
The literature provides conflicting data on the presence of seasonality of infection caused by the Epstein-Barr virus (EBV). The aim of the work was to assess the annual dynamics of the incidence of infectious mononucleosis in Moscow. Materials and methods. The analysis was carried out according to the official statistics and the results of laboratory studies (IgM VCA, IgG EA, EBV DNA in blood and saliva), conducted in the branches of LLC “Independent laboratory INVITRO” for the period 2014-2018. Were used conventional statistical methods. Results. Identified: seasonal rise in the incidence of infectious mononucleosis in the cold season with two peaks in autumn and spring; the presence of a strong direct correlation between the annual incidence and the frequency of detection of EBV DNA in the blood, IgM VCA, IgG EA per 100 thousand population; the distribution of detectability of markers per 100 examined from the maximum to the minimum (EBV DNA in saliva, IgG EA, IgM VCA, EBV DNA in the blood); a significant excess of detectability IgG EA, IgM VCA and EBV DNA in blood per 100 examined in the warm season; the presence in the annual dynamics of the frequency of detection of EBV DNA in saliva per 100 thousand population seasonal rise from October to June, reflecting the presence of sources of infection in the population. Conclusion. The use of indicators of the frequency of detection of markers of acute EBV infection allowed with a high probability to determine the presence of two seasonal wave rise in morbidity, which did not allow making official statistics that do not take into account the results of laboratory studies.